Epidemiological and clinical outlook of chronic Chagas’ heart disease in Mexico - Sierra-Johnson, Justo; Olivera-Mar, Amonario; Monteón-Padilla, Víctor M; Reyes, Pedro A; Vallejo, Maite (Revista de Saúde Pública, 2005)
OBJECTIVE: To compare the epidemiological and clinical characteristics of chronic Chagas' heart disease to other dilated cardiomyopathies. METHODS: A study comprising 128 patients from a heart disease center was carried out from 1993 to 2003. Of them, 51 (40%) were Trypasonoma cruzi positive. Epidemiological data was obtained through interviews and clinical and serological data from health services. Statistic analysis was conducted using the Chi-square, Fischer, Mann-Whitney or Students' t-test as well as multivariate analysis. RESULTS: Chronic Chagas' disease patients were older (55±10 years old) than those patients with cardiopathy (42±17 years old). Most of them were born in rural areas (90% vs 68%), lived in poor (75% vs 16%), crowded households (45% vs 20%), together with domestic animals (71% vs 61%) and were aware of the Chagas' vector (73% vs 25%). Rhythm and conduction ECG abnormalities as well as permanent pacemaker were common among Chagas' patients (84% vs 55%, 78% vs 64% and 24% vs 10%, respectively). Congestive heart failure was more frequent among cardiomiopathy patients (88% vs 71%). Both groups had abnormal myocardial perfusion with normal epicardial arteries. Comorbidities were more frequent in cardiomiopathy patients than in chronic Chagas' disease patient (two cases only). CONCLUSIONS: Chagas' disease is the most common cause of dilated cardiomiopathy in the study hospital. Due to its regional distribution in Mexico, it deserves special attention and control programs proven to be effective in other countries.